Mucociliary Clearance Scans Show Infants Undergoing Congenital Cardiac Surgery Have Poor Airway Clearance Function - Adams, Phillip S.; Corcoran, Timothy E.; Lin, Jiuann-Huey; Weiner, Daniel J.; Sanchez-de-Toledo, Joan; Lo, Cecilia W. (Frontiers in Cardiovascular Medicine, 2021)
Background: Infants undergoing congenital cardiac surgery with cardiopulmonary bypass are at high risk for respiratory complications. As impaired airway mucociliary clearance (MCC) can potentially contribute to pulmonary morbidity, our study objective was to measure airway clearance in infants undergoing congenital cardiac surgery and examine correlation with clinical covariables that may impair airway clearance function. Materials and Methods: Airway clearance in infants was measured over 30 min using inhaled nebulized Technetium 99m sulfur colloid administered either via a nasal cannula or the endotracheal tube in intubated infants This was conducted bedside with a portable gamma camera. No difficulty was encountered in positioning the gamma camera over the patient, and neither the camera nor the MCC scan interfered with routine medical care or caused any adverse events. Patient and perioperative variables were examined relative to the MCC measurements. Results: We prospectively enrolled 57 infants undergoing congenital cardiac surgery and conducted a single MCC scan per patient. MCC data from 42 patients were analyzable, including 5 preoperative, 15 (40.5%) in the immediate postoperative period (days 1–2), and 22 (59.5%) were later postoperative (≥3 days). Preoperative MCC was inversely proportional to days requiring postoperative mechanical ventilation (p=0.006) and non-invasive positive pressure ventilation (p=0.017). MCC was higher at later postoperative days (p=0.002), with immediate postoperative MCC being lower (3%; 0–13%) than either preoperative (21%; 4–25%) (p=0.091) or later postoperative MCC (18%; 0–29%) (p=0.054). Among the infants with low postoperative MCC, significantly more were premature (5/19 (26%) vs. 0/18 (0%); p=0.046), were intubated (14/19 (75%) vs. only 7/18 (39%); p=0.033), and were receiving higher FiO2 (40%, 27–47% vs. 26%, 21–37; p=0.015). Conclusions: This is the first study to show that infants undergoing congenital cardiac surgery have impaired MCC. MCC appeared lowest in the immediate postoperative period. Worse MCC was associated with prematurity, mechanical ventilation, or receiving higher FiO2. These findings suggest MCC scans should be further explored for informing clinical decision making to improve postsurgical outcomes. The possible therapeutic benefit of airway clearance maneuvers for infants with poor MCC function should also be investigated.